2001
DOI: 10.1063/1.1410330
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and piezoelectric response of lead zirconate–lead titanate at high electric and mechanical loads in terms of non-180° domain wall motion

Abstract: The effect of prestress on the nonlinear dielectric (polarization) and piezoelectric (strain) response of lead zirconate–lead titanate (PZT–5H) piezoelectric ceramic is studied. The response to bipolar (−2/+2 MV/m) and unipolar (0/+2 MV/m, −0.4/+2 MV/m) electric field under constant prestress (up to 175 MPa) is experimentally evaluated. In the bipolar regime, prestress mainly influences the first non-180° process. In the unipolar regime, the dielectric and piezoelectric response achieve maximum values near 50–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 11 publications
6
80
0
2
Order By: Relevance
“…Hence, the electric field is not higher than 10 −3 kV/cm at low frequency, and the electrical current is lower than 10 ma even at resonance. These values are low enough so that the extrinsic effect is not perturbed by the nonlinear behavior that appears in PZT when high electrical or mechanical fields are applied [5]. resonance and antiresonance frequencies of the main vibration extensional mode were measured at each temperature.…”
Section: B Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the electric field is not higher than 10 −3 kV/cm at low frequency, and the electrical current is lower than 10 ma even at resonance. These values are low enough so that the extrinsic effect is not perturbed by the nonlinear behavior that appears in PZT when high electrical or mechanical fields are applied [5]. resonance and antiresonance frequencies of the main vibration extensional mode were measured at each temperature.…”
Section: B Measurement Methodsmentioning
confidence: 99%
“…The first, called the intrinsic effect, is related to the polarization of the elemental cell and would be the sole response if the material was in a single domain state. The second, known as the extrinsic effect, includes all the phenomena different from the intrinsic effect, although it is commonly accepted in the literature that the major contribution to the extrinsic effect comes from the motion of the domain walls and their interaction with the lattice defects [3]- [5]. Zhang et al have shown that the intrinsic contribution to the material response can be considered nearly constant with the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…8 External mechanical compressive stress has been found to strongly influence switching, 9,10 either suppressing or assisting domain reorientation processes. 4,[11][12][13][14][15][16][17][18][19][20][21][22] If the external applied stress is large enough domain switching may be suppressed completely. 12,14 However, small mechanical compressive stresses can also prompt an increase in ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…12,14 However, small mechanical compressive stresses can also prompt an increase in ferroelectric properties. 4,5,16,19,20 Depending on the orientation of the mechanical load it is possible to improve the domain switching ability of polycrystalline 21,22 and single crystal ferroelectrics. 23 The influence of mechanical load is not limited to external stress; intrinsic internal stress has also been found to influence the switching behavior of ferroelectric materials.…”
Section: Introductionmentioning
confidence: 99%
“…There are basically three combinations for the electrical and mechanical loadings: ͑1͒ alternating electric field and static stress, ͑2͒ alternating stress and dc field, and ͑3͒ both alternating field and stress with an arbitrary phase difference. Lynch, 11 Chaplya,12 and Zhou et al 5 studied the effect of static stress on the polarization and strain of a PZT ceramic driven by an alternating electric field. They observed that both the remanent polarization and spontaneous strain are suppressed under a large longitudinal compressive stress.…”
Section: Introductionmentioning
confidence: 99%